Answer
The solutions are \( x = \frac{1}{4} + \frac{i\sqrt{327}}{12} \) and \( x = \frac{1}{4} - \frac{i\sqrt{327}}{12} \).
Solution
To solve the equation \( -6 x^{2} = -3 x + 14 \) using the quadratic formula, we first need to rearrange it into the standard form \( ax^2 + bx + c = 0 \).
1. **Rearranging the equation:**
\[
-6x^2 + 3x - 14 = 0
\]
This gives us:
- \( a = -6 \)
- \( b = 3 \)
- \( c = -14 \)
2. **Using the quadratic formula:**
The quadratic formula is given by:
\[
x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}
\]
3. **Calculating the discriminant:**
First, we calculate \( b^2 - 4ac \):
\[
b^2 - 4ac = 3^2 - 4(-6)(-14)
\]
Now, let's calculate this step by step.
- Calculate \( 3^2 \):
\[
3^2 = 9
\]
- Calculate \( 4 \times -6 \times -14 \):
\[
4 \times -6 \times -14 = 336
\]
- Now, substitute these values into the discriminant:
\[
9 - 336 = -327
\]
Since the discriminant is negative, this indicates that the equation has no real solutions, but two complex solutions.
4. **Calculating the solutions:**
We will now calculate the complex solutions using the quadratic formula:
\[
x = \frac{-3 \pm \sqrt{-327}}{2 \times -6}
\]
Let's calculate this.
- The square root of \(-327\) can be expressed as:
\[
\sqrt{-327} = i\sqrt{327}
\]
Now, we can substitute this back into the formula:
\[
x = \frac{-3 \pm i\sqrt{327}}{-12}
\]
This simplifies to:
\[
x = \frac{3}{12} \mp \frac{i\sqrt{327}}{12}
\]
\[
x = \frac{1}{4} \mp \frac{i\sqrt{327}}{12}
\]
Thus, the solutions to the equation \( -6 x^{2} = -3 x + 14 \) are:
\[
x = \frac{1}{4} + \frac{i\sqrt{327}}{12} \quad \text{and} \quad x = \frac{1}{4} - \frac{i\sqrt{327}}{12}
\]
Reviewed and approved by the UpStudy tutoring team
Explain
Simplify this solution